2008
DOI: 10.1016/j.febslet.2008.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of SIRT1 protein levels by nutrient availability

Abstract: The mammalian NAD+ dependent deacetylase, SIRT1, was shown to be a key protein in regulating glucose homeostasis, and was implicated in the response to calorie restriction. We show here that levels of SIRT1 increased in response to nutrient deprivation in cultured cells, and in multiple tissues of mice after fasting. The increase in SIRT1 levels was due to stabilization of SIRT1 protein, and not an increase in SIRT1 mRNA. In addition, p53 negatively regulated SIRT1 levels under normal growth conditions and is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
2
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 32 publications
7
69
2
3
Order By: Relevance
“…More strikingly, Sajish and Schimmel recently found that serum starvation or resveratrol addition promotes the nuclear translocation of TyrRS, which enhances the interaction of TyrRS with PARP1 and increases the PARP1 activity (6). However, serum starvation increases SIRT1 protein expression, thereby inhibiting the function of PARP1 (16,40). Thus, the function of this regulatory network remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…More strikingly, Sajish and Schimmel recently found that serum starvation or resveratrol addition promotes the nuclear translocation of TyrRS, which enhances the interaction of TyrRS with PARP1 and increases the PARP1 activity (6). However, serum starvation increases SIRT1 protein expression, thereby inhibiting the function of PARP1 (16,40). Thus, the function of this regulatory network remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…9, A and B). Likewise, nutrient depletion activates Sirt1, an upstream activator of FoxO transcription factors both in vitro and in vivo (47,48). Sirt1 protein was significantly increased (1.5-fold) in the starved mouse heart compared with fed mouse heart (Fig.…”
Section: Starvation Activates Foxo Transcription Factors and Induces mentioning
confidence: 97%
“…We observed that 48-h-fasting induced decreased T 3 and T 4 levels and increased hepatic SIRT1 content. Other reports in the literature have already described, independently, fasting-induced decreased TH levels (Diano et al 1998, Hashimoto et al 2001) and hepatic SIRT1 content increment (Rodgers et al 2005, Kanfi et al 2008. Reduced TH concentration serves to conserve energy, as these hormones are important stimulators of basal metabolism and thermogenesis (Klieverik et al 2009).…”
Section: Sirt1 Regulation By Th Involves Trbmentioning
confidence: 99%
“…It is very well established that physiological adaptation to fasting involves the suppression of TH production, as a mechanism to conserve energy (Boelen et al 2008). In addition, recent studies have shown the fasting-induced rise in SIRT1 expression in several tissues (Rodgers et al 2005, Kanfi et al 2008. Therefore, the existence of common metabolic routes regulated by TH and SIRT1, together with the inverse correlation of these factors' variation during calorie deprivation, led us to investigate whether SIRT1 expression is regulated by TH in mice and the possible interactions of TH and SIRT1 during energy deprivation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation